2022
DOI: 10.1176/appi.ajp.2021.20050630
|View full text |Cite
|
Sign up to set email alerts
|

Interindividual Differences in Cortical Thickness and Their Genomic Underpinnings in Autism Spectrum Disorder

Abstract: Objective. Autism Spectrum Disorder (ASD) is accompanied by highly individualized neuroanatomical deviations that potentially map onto distinct genotypes and clinical phenotypes. However, the link between biological pathways and differences in brain anatomy, which may pave the way towards targeted therapeutic interventions, remains poorly understood.Methods. Our study examined neurodevelopmental differences in cortical thickness (CT) and their genomic underpinnings in a large and clinically diverse sample of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
25
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 54 publications
10
25
2
Order By: Relevance
“…A recent study by Romero-Garcia et al (2019) demonstrated that differences in cortical thickness (CT) during childhood were robustly associated with genes involved in synaptic transmission pathways, which are known to be downregulated in the postmortem ASD cortex [ 42 , 66 ]. Similar results were also recently reported by our group when examining CT differences in ASD in a large and clinically heterogeneous sample [ 67 ]. The present results converge with these previous findings, as we observed an enrichment for genes and coexpressed modules that are known to be downregulated in ASD.…”
Section: Discussionsupporting
confidence: 91%
“…A recent study by Romero-Garcia et al (2019) demonstrated that differences in cortical thickness (CT) during childhood were robustly associated with genes involved in synaptic transmission pathways, which are known to be downregulated in the postmortem ASD cortex [ 42 , 66 ]. Similar results were also recently reported by our group when examining CT differences in ASD in a large and clinically heterogeneous sample [ 67 ]. The present results converge with these previous findings, as we observed an enrichment for genes and coexpressed modules that are known to be downregulated in ASD.…”
Section: Discussionsupporting
confidence: 91%
“…Despite many reports of group differences in cortical thickness (60,61), we did not show any significant differences between autistic and control participants in our study. However, we found that regions where GABAergic - but not glutamatergic - genes were increasingly expressed in the normative brain showed larger differences in cortical thickness between our autism and control participants.…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, the observed differences in cortical thinning correlated with synaptic genes [ 21 ]. These findings echo previous observations, indicating an association between synaptic genes and differences in cortical thickness in individuals with ASD [ 22 , 23 ]. Bieneck et al, reported altered cortical thinning predominantly in fronto-temporal brain regions and the cingulate cortex in individuals with ASD [ 21 ].…”
supporting
confidence: 91%